‘Tobolyak’: an oat cultivar for universal use - M. N. Fomina; Yu. S. Ivanova; O. A. Pay; N. A. Bragin (Труды по прикладной ботанике, генетике и селекции)
Background. An urgent problem is the development and introduction of cultivars for universal use that can meet the demand of animal husbandry for various types of feed and that of food industry for raw materials. Of great interest in this regard is ‘Tobolyak’, a new spring oat cultivar characterized by a high yield of grain and green biomass.Materials and methods. The cultivar was developed at the Research Institute of Agriculture for the Northern TransUrals, a branch of the Tyumen Scientific Centre, Siberian Branch of the RAS, using hybridization techniques with subsequent selection. The cultivars used as source material for hybridization were ‘Tayoznik’ (Narym Agricultural Station, Tomsk Province) and ‘Orion’ (Siberian Research Institute of Agriculture, Omsk Province).Results. It is a mid-ripening cultivar, with the growing season of 71 to 83 days from sprouting to wax ripeness; its plants are medium-tall (89.6 to 120.2 cm), and resistant to lodging. The average grain yield for the years of study (2014–2019) under the environmental conditions of the northern forest-steppe (Tyumen Province) was 5.88 t/ha (+0.41 t/ha to the reference). The maximum grain yield (7.97 t/ha) was obtained in 2019 at the Lower Tavda Variety Testing Plot, Tyumen Province. The cultivar formed a grain with the test weight of 459.5–527.0 g/l and a low hull content of 22.1–25.1%. The yield of green biomass varied from 31.4 to 47.3 t/ha, depending on the growing conditions, and averaged 37.7 t/ha in 2014–2019 (+7.3 t/ha to the reference). Dry matter harvest averaged 11.76 t/ha (+1.54 t/ha to the reference), ranging from 8.62 to 14.56 t/ha.Conclusion. The new spring oat cultivar ‘Tobolyak’ for universal use has been listed the State Register for Selection Achievements since 2020 and recommended for cultivation in regions 10, 11 and 12 of the Russian Federation.